(untitled) (The Strategic Review for Southern Africa, 2020)
This year will focus on celebrations and reflections on occasion of the 70th anniversary of the United Nations. At the same time, the Millennium Development Goals as well as the Sustainable Development Goals for thepost-2015 era remain central items on the agenda when global governance issues and international responsibilities are discussed.Notions, which by implication always also carry a local meaning and impact on domestic policy in as much as domestic policy (not only as foreign policy) also impacts on global governance issues. The divide often maintained is more than ever artificial and misleading in the face of the global challenges humanity faces — not only in terms of environmental degradation as a resultof climate change. Many issues do not have any territorial boundaries orare transcending those. The inter-linkages of the local and the global (for which the term'glocal' was minted a few years ago) are obvious not only when it comes tohumanitarian disasters and emergency situations appealing to globalsolidarity, such as the recent earthquake in Nepal and its devastating consequences. Other manifestations of solidarity in a global world include the almost world-wide 'Je Suis Charlie' response and outcry to the terrorist attack on the journal and the cold-blooded execution of its cartoonists in Paris. The gathering of world leaders there in defiance of the assault on civil liberties and freedoms of expression was a symbolic act of some magnitude and brought together even deeply antagonistic political players. But at the same time the lack of similar visible and determined symbolic acts of defiance by the world's political leaders and Western civil society agencies, suggesting an absence of a similar degree of moral outcry and global protest over the ongoing slaughters and abductions by Boko Haram in Nigeria or the massacre of students at the Garissa University College in Kenya seem to suggest that we still live in times of double standards and/or selective perceptions. Humanity as well as humanbeings remain divided and seem to live in different worlds. Likewise, the tragedies taking place visibly in broad daylight on the Mediterranean Sea, reaching a scale of human loss at days bordering to the numerical proportions of 9/11, have not been met with a similar rigorous political will topromote true values of humanity.